Internal Promotion or External Hire? Staffing Management Positions When Employees Have a Seat in the Boardroom - Aleksandra Gregoric; Takao Kato; Casper B.L. Larsen (Institute of Labor Economics (IZA), 2024)
We join the scholarly conversation on the implications of the different configurations of firms' stakeholder coalitions for their employment practices, by investigating how the structural arrangements granting employees a role in firm boards of directors (employee governance representation, EGR) affect firms' propensity to staff management positions through external labor markets rather than internal promotions. The literature has thus far pointed to a possible workers' impact on employment practices primarily through the power mechanism, contingent on the employees' ability to enforce their preferences with regard to hiring and other employment practices. We contribute to this scholarly work by (1) explicating why employees likely prefer firms to rely on internal labor markets (ILM) when hiring new managers and (2) conceptualizing the employees' impact on the staffing of management positions via the efficiency mechanism, related to the positive effects of EGR on the functioning of the ILM. We provide support for our hypotheses, using linked employer-employee data for Danish firms during 2001-2017.
Keywords: M5; 330; employee representation; corporate governance; hiring practices; internal labor markets; management jobs